2017
DOI: 10.1002/rcm.8027
|View full text |Cite
|
Sign up to set email alerts
|

High‐energy collision‐induced dissociation of histidine ions [His + H]+ and [His − H] and histidine dimer [His2 + H]+

Abstract: The KER for HCOOH loss from both [His + H] and [His - H] is similar at 278 and 249 meV, respectively, which suggests that the collision-induced dissociation takes place via a similar mechanism. The loss of COOH and C H NO from the dimer suggests that the dimer of His binds through a shared proton between the imidazole moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…27 The evaluated KER for this dissociation channel amounts to 339 meV, which is lower than the KER reported for simple nitroimidazoles of nearly 1 eV. 27 Due to the high internal energy content of the electrosprayed ions observed already previously for this experimental setup, 35 the main product ion of m/z 140 is also visible in the ESI. The high-energy CID of mass selected m/z 140 (Figure S1 of the Supporting Information) showed that the product ion at m/z 94 is also formed from further dissociation of m/z 140 likely through the loss of a complete NO2 • group.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…27 The evaluated KER for this dissociation channel amounts to 339 meV, which is lower than the KER reported for simple nitroimidazoles of nearly 1 eV. 27 Due to the high internal energy content of the electrosprayed ions observed already previously for this experimental setup, 35 the main product ion of m/z 140 is also visible in the ESI. The high-energy CID of mass selected m/z 140 (Figure S1 of the Supporting Information) showed that the product ion at m/z 94 is also formed from further dissociation of m/z 140 likely through the loss of a complete NO2 • group.…”
Section: Resultsmentioning
confidence: 73%
“…Analytical Ltd., Manchester, UK). The ESI source, as well as the mass spectrometer were already described in detail elsewhere, 35 therefore only a brief description will be provided. The ions were produced by ESI, 36 where ionization occurs by applying a voltage ranging from +4.75 kV to +5.01 kV on the spray needle with respect to the inlet capillary (inner diameter of 750 µm).…”
Section: High-energy Cidmentioning
confidence: 99%